2013
DOI: 10.1080/21672857.2013.11519725
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological consequences of gravity with spin and torsion

Abstract: We show that the Einstein-Cartan-Sciama-Kibble theory of gravity with torsion not only extends general relativity to account for the intrinsic spin of matter, but it may also eliminate major problems in gravitational physics and answer major questions in cosmology. These problems and questions include: the origin of the Universe, the existence of singularities in black holes, the nature of inflation and dark energy, the origin of the matter-antimatter asymmetry in the Universe, and the nature of dark matter.Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…We will prove that such non-minimal couplings will even be super-renormalizable. Moreover, for consistency with the existing literature, we will show that the presented theory preserves the results on the avoidance of cosmological singularities, which have been already established [3,[5][6][7][8][9][10]. The paper will be divided in the following way: Section II is dedicated to the description of the theory and its general properties, particularly the conservation laws; Section III is instead dedicated to some interesting aspects of the theory such as renormalizability and parity violation; Section IV is devoted to cosmological considerations; Section V is dedicated to the summary of the results, and an overall discussion as conclusion.…”
Section: Introductionsupporting
confidence: 84%
“…We will prove that such non-minimal couplings will even be super-renormalizable. Moreover, for consistency with the existing literature, we will show that the presented theory preserves the results on the avoidance of cosmological singularities, which have been already established [3,[5][6][7][8][9][10]. The paper will be divided in the following way: Section II is dedicated to the description of the theory and its general properties, particularly the conservation laws; Section III is instead dedicated to some interesting aspects of the theory such as renormalizability and parity violation; Section IV is devoted to cosmological considerations; Section V is dedicated to the summary of the results, and an overall discussion as conclusion.…”
Section: Introductionsupporting
confidence: 84%
“…The spin effects can be negligible at the early stages of the collapse, while as the collapse proceeds, these effects would play a significant role in the final fate of the scenario of the collapse. This situation can be compared to the singularity removal for a FLRW spacetime in the very early universe, as we go backwards in time [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. We showed that in contrast to the homogeneous dust collapse which leads inevitably to the formation of a spacetime singularity, the occurrence of such a singularity is avoided and instead a bounce occurs at the end of the contracting phase.…”
Section: Discussionmentioning
confidence: 99%
“…Substituting for the torsion tensor, from Eq. (5), into these terms we get the combined field equations [38,39,53,54,[62][63][64][65][66]:…”
Section: Einstein-cartan Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…When the space has torsion, the generalised Bianchi identities are also known as the Weitzenbock identities and take the form (e.g. see [20])…”
Section: The Bianchi Identitiesmentioning
confidence: 99%